Evolutionary progression and functional diversification of NAC family members in pearl millet with comprehensive characterization of PgNAC103 under drought stress - Deepak Kumar Jha; Jeky Chanwala; I. Sriram Sandeep; Preeti Barla; Nrisingha Dey (Plant Stress, 2025)
This study investigated the role of NAC transcription factors (TFs) in the stress response of pearl millet, a C4 crop known for its nutritional value and drought tolerance. Phylogenetic and synteny analysis of 155 NAC TFs revealed the contribution of segmental duplication to NAC gene evolution. Promoter analysis identified various stress-related cis-elements in the upstream regions of these genes. We analysed expression pattern of identified NAC genes under phytohormones (ABA, MeJA, and SA) and abiotic stresses (drought, salinity, and heat). PgNAC103 was found to be a nuclear protein having a C-terminal transactivation domain. Arabidopsis and pearl millet overexpressing the PgNAC103 showed enhanced stress responses under drought. Transgenic lines showed less sensitivity towards ABA treatment. In transgenic Arabidopsis, the drought stress response was manifested through the upregulation of stress marker genes (RD22, KIN1, COR15A) and increased ROS scavenging (SOD, POD and CAT). The transcriptional activity of the PgNAC103 promoter was induced by drought stress in transgenic plants. These findings suggest that NAC TFs function as positive or negative regulators of the abiotic stress response in pearl millet, with PgNAC103 specifically acting as a positive regulator of drought stress tolerance. PgNAC103 represents a promising genetic resource for developing climate-resilient crops.